Successful sofosbuvir treatment with ribavirin dose reduction for chronic hepatitis C virus genotype 2 infection in a patient with ulcerative colitis: a case report. Issue 1 (December 2016) - Ohta, Yuki; Kanda, Tatsuo; Katsuno, Tatsuro; Yasui, Shin; Haga, Yuki; Sasaki, Reina; Nakamura, Masato; Wu, Shuang; Nakamoto, Shingo; Arai, Makoto; Yokosuka, Osamu
Abstract Background Ulcerative colitis is a lifelong, immunologically mediated disease. Direct-acting antivirals (DAAs) are now available for the treatment of chronic hepatitis C virus (HCV) infection. An interferon-free regimen appears useful, safe and effective for many patients for whom interferon-based treatment is contraindicated. Case presentation We studied a 56-year-old treatment-naïve Japanese man with chronic HCV genotype 2b infection who had ulcerative colitis. This patient was treated with sofosbuvir and ribavirin for 12 weeks. During treatment, diarrhoea and bloody faeces were frequent. After ribavirin was reduced to 400 mg daily, these symptoms decreased. Finally, the patient achieved a sustained virologic response 12 weeks after the stoppage of the treatment. Conclusion Clinicians should pay careful attention to the ribavirin dose in the treatment of certain HCV patients with inflammatory bowel disease who are receiving sofosbuvir plus ribavirin.